Development of Local History Learning with the Heroism Theme of K. Gholib Based on E-Book for Private Vocational School Students in Pringsewu Regency - Yoga Fernando Rizqi; Djono Djono; Susanto Susanto (BIRCU, 2020)
The purpose of this research is to discuss the development of material that supports the history of the struggle of K.H Gholib, who then compiles it into an e-book using the software